Anti-Obesity Effects of Arum maculatum, Nasturtium officinale Plant Extracts and Exercise in High Fat Diet-Induced Obese Rats - Ibrahim, Zana Hassan (Kurdistan Journal of Applied Research, 2022)
ABSTRACT The Aim: To investigate and distinguish the anti-obesity activities of Arum maculatum, Nasturtium officinale plant extracts and exercise against high-fat diet induced obesity at rat model. Methods: Thirty healthy male albino rats were randomly separated into 5 groups (n=6): Normal control (NC), high-fat diet control (HFD-C), Arum maculatum extract (AME), Nasturtium officinale extract (NOE) and exercise. The NC group fed with normal diet (ND) and all other groups a high fat diet (HFD) to induce obesity and hyperlipidemia for 8 weeks. Corresponding treatments were established to the respective groups during study period. Rat body weights (BW) and food intake were obtained weekly. Glucose, Total cholesterol (TC), triglycerides (TG), low, very low and high-density lipoprotein cholesterols (LDL-C, VLDL-C and HDL-C), malondialdehyde (MDA) with aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were estimated in serum at the end of the study. Results: The HFD-C rats were associated with a significant increase (P<0.05) in BW gain with the elevations in serum glucose, lipid profiles (TC, TG, LDL-C &VLDL-C), liver function tests (AST & ALT) and MDA in comparison with NC rats whereas the level of serum HDL-C decreased. Furthermore, treatments of AME, NOE and exercise along with HFD significantly (P<0.05) reduced HFD-induced changes in BW gain and the levels of serum biochemical parameters as compared to rats fed HFD. The most significant effect on reducing weight gain at model rats were recorded by NOE treatment, while the attenuated effects AME on BW gain and AST, exercise on BW gain, TG, VLDL, MDA and AST were not significant (P>0.05). Conclusions: Consumption of HFD for 8 weeks caused HFD-C rats obese, hyperglycemic and hyperlipidemic with hepatic cellular injury when compared to the NC rats. AME, NOE and exercise treatments were suppressed the development of obesity as well as attenuated HFD induced changes in serum biochemical parameters of the respective groups when compared to the HFD-C group.